The Impact of Foreign Variables in Counterterrorism Efforts in Iraq (قضايا سياسية, 2024)
In this study, an attempt was made to monitor the impact of the external variable, whether from states or specialized organizations in efforts to combat terrorism in Iraq. The study was launched from the logic that the external variable played an important role in ending terrorism in Iraq, but this role is supposed to be changing following the status quo. In order to verify this assumption, multiple approaches were used, including the historical descriptive approach, as well as the deductive analytical approach based on the facts, outcomes, and tracking phenomenon. The study reached out to number of conclusions, including that the effectiveness of the external variable in the war on terrorism is characterized by change, and instability in its vision and practices according to what its own interests dictate, and based on that Iraq need to orginaze the external variable’s role in the war against terrorism, as well institutional adaptation according to national in interest as a requirement of sovereignty.